Mechanisms of Alignment in Feeding Aphids on the Plant Stem - Ayumi Kudo (Ecology and Evolution)
ABSTRACT Aphids are observed on various plant species, with most aphids feeding downward on stems. In this study, I studied the variations in feeding postures of aphids and their mechanisms. My field observations revealed that the majority of individuals from most species fed facing downward, or more precisely, towards the roots. Exceptions included Indomegoura indica on the scapes of Hemerocallis spp., which were aligned with their head facing the sky. Next, I investigated how plant orientation affects three aphid species, Macrosiphoniella yomogifoliae, Megoura crassicauda and I. indica with different body alignments on upright immature stems. On the stems of the inverted plants, the number of Ma. yomogifoliae and Me. crassicauda in the upward position (head facing the root of the plant) was significantly greater than that in the downward position (head facing the shoot apex of the plant). If their posture is affected by gravity or by certain advantages of the headstand posture, Ma. yomogifoliae and Me. crassicauda are expected to align in a consistent direction, regardless of the orientation of the plant. This suggests that plant cues influence their posture. In contrast, the majority of I. indica were aligned with the head facing the sky on the scape, regardless of Hemerocallis's direction. This result indicates that the feeding posture of I. indica is affected by gravity and/or aphid's intrinsic factors. Therefore, this study provides a new perspective on the factors influencing aphid feeding posture preferences.